A simple, quick and novel protocol for biaryl synthesis using LiCl‐promoted in situ‐generated Pd nanoparticles. (5th September 2017) - Phukan, Parmita; Boruah, Preeti Rekha; Gehlot, Praveen Singh; Kumar, Arvind; Sarma, Diganta
Abstract: This paper describes a simple and a very quick protocol for biaryl synthesis using the Suzuki–Miyaura cross‐coupling reaction. A quintessential role of salting‐out agent LiCl was observed in the Suzuki–Miyaura cross‐coupling reaction that enhanced the reduction rate of Pd (II) to a considerable extent, resulting in the formation of nanosized palladium in a few seconds. The isolated Pd nanoparticles were characterized with X‐ray diffraction, dynamic light scattering, TGA, transmission electron microscopy and scanning electron microscopy‐dispersive X‐ray spectroscopy. The Suzuki–Miyaura cross‐coupling reaction proceeded very well with the in situ‐ generated Pd nanocatalysts furnishing the desired biaryl adducts with excellent yields. Abstract : This paper describes a simple and a quick protocol for biaryl synthesis using Suzuki‐Miyaura cross coupling reaction. A quintessential role of salting out agent LiCl was observed in the Suzuki‐Miyaura cross‐coupling reaction that enhanced the reduction rate of Pd (II) to a considerable extent affording nanosized palladium in a few seconds. The isolated Pd NPs were characterized with XRD, DLS, TGA, TEM, and SEM‐EDX. Suzuki cross‐coupling reaction proceeded very well with Pd‐nano catalysts furnishing the desired biaryls with excellent yields.